Water and Sediment Budget of Casiquiare Channel Linking Orinoco and Amazon Catchments, Venezuela - Alain Laraque (Water, 2019)
The Casiquiare River is a natural channel that connects two of the greatest rivers in the world, the Orinoco and the Amazon in the South American continent. The aim of this paper is to present a review and synthesis of the hydrological and sedimentological knowledge of the Casiquiare River, including the first hydro-sedimentary balance of the Casiquiare fluvial system conducted 9−12 September 2000 at the bifurcation and mouth during the expedition ‘Humboldt-Amazonia 2000’. Bathymetric flow discharge and physico-chemical measurements were made at the inlet and outlet of the Casiquiare Channel. The main conclusions of this study indicate that Casiquiare is taking a significant proportion of flow (20% to 30%) from the Upper Orinoco basin to the Amazon basin. Throughout its 356 km-course, this chameleon channel undergoes significant morphological, hydrological, and bio-geochemical variations between the inlet and outlet, whose most visible witnesses are the increase in its width (3 to 4 times), flow (7 to 9 times), and its change in water color (white to black water), under the influence of tributaries coming from vast forest plains.